Non-pharmacological Approaches to Depressed Elderly With No or Mild Cognitive Impairment in Long-Term Care Facilities. A Systematic Review of the Literature - Gramaglia, Carla; Gattoni, Eleonora; Marangon, Debora; Concina, Diego; Grossini, Elena; Rinaldi, Carmela; Panella, Massimiliano; Zeppegno, Patrizia (Frontiers in Public Health, 2021)
Introduction Compared to old people who live at home, depressive symptoms are more prevalent in those who live in long-term care facilities (LTCFs). Different kinds of non-pharmacological treatment approaches in LTCFs have been studied, including behavioural and cognitive-behavioural therapy, cognitive bibliotherapy, problem-solving therapy, brief psychodynamic therapy and life review/reminiscence. The aim of the current review was to systematically review non-pharmacological treatments used to treat depressed older adults with no or mild cognitive impairment (as described by a Mini Mental State Examination score > 20) living in LTCFs. Methods A research was performed on PubMed and Scopus databases. Following the Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA) flowchart, studies selection was made. The quality of each Randomized Controlled Trial was scored using the Jadad scale, Quasi-Experimental Design studies and Non-Experimental studies were scored based on the Newcastle-Ottawa Scale (NOS) Results The review included 56 full text articles; according to the type of intervention, studies were grouped in the following areas: horticulture/gardening (n=3), pet therapy (n=4), physical exercise (n=9), psychoeducation/rehabilitation (n=15), psychotherapy (n=3), reminiscence and story sharing (n=14), miscellaneous (n=8). Discussion and conclusion Despite mixed or negative findings in some cases, most studies included in this systematic review reported that the non-pharmacological interventions assessed were effective in the management of depressed elderly in the LTCFs context. Regrettably, the limitations and heterogeneity of the studies described above hinder the possibility to generalize and replicate results.